2016
DOI: 10.3233/bmr-150644
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular dysfunction and risk factors for anxiety and depression

Abstract: Among the patients with TMD, the groups who were considered to have anxiety and depression were female patients, patients with deficient social support system, and patients with myofacial pain alone or patients with myofacial pain accompanying an existing TMJ disorder. The existence of anxiety and depression should be considered in addition to musculoskeletal pathologies during the treatment plan of patients with TMJ who have these risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 17 publications
0
40
0
6
Order By: Relevance
“…Diracoglu (2016) revealed in his study that, among the patients with TMD, the groups who were considered to have anxiety and depression were female patients, patients with deficient social support system, and patients with myofacial pain alone or patients with myofacial pain accompanying an existing TMJ disorder. 16 Both the women and men TMD patients in the present study reported significantly more and/or more frequent somatic, psychologic, and behavioral symptoms on the Beck's Depression Inventory, on average. Thus, there is some justification for concluding that the results of prior studies using largely female TMD patient samples might be generalized to male TMD patient samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diracoglu (2016) revealed in his study that, among the patients with TMD, the groups who were considered to have anxiety and depression were female patients, patients with deficient social support system, and patients with myofacial pain alone or patients with myofacial pain accompanying an existing TMJ disorder. 16 Both the women and men TMD patients in the present study reported significantly more and/or more frequent somatic, psychologic, and behavioral symptoms on the Beck's Depression Inventory, on average. Thus, there is some justification for concluding that the results of prior studies using largely female TMD patient samples might be generalized to male TMD patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Data was entered in SPSS. We also categorized patients in [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] year age group and the 31-50 year age group. Chi-square test was used to determine statistically significant difference in level of depression among age groups and male female patients (p<0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Embora ambas as avaliações representem percepções subjetivas, parece não haver correlação entre a intensidade e a sensibilidade à dor, pois a hipótese de que elevada intensidade de dor estivesse relacionada à elevada sensibilidade à dor não foi demonstrada em estudo prévio (SANCHES et al, 2015), concordando com os resultados obtidos neste estudo. Lauche et al (2014) (REISSMANN et al, 2014;DIRAÇOǦLU et al, 2016).…”
Section: Sensibilidade à Dor (Limiar De Dor à Pressão)unclassified
“…Os fatores emocionais como a catastrofização da dor e a ansiedade podem influenciar na expressão deste processo de controle da dor, aumentando a sensibilização nociceptiva (DIRAÇOǦLU et al, 2016;NAHMAN-AVERBUCH et al, 2016). A ansiedade tem sido apontada como um fator preditivo da percepção de dor, enquanto outros fatores como gênero, depressão, estresse, amplificação somatossensorial, idade e peso parecem não ter relação direta com os níveis de intensidade de dor referida, porém influenciam a sensibilização nociceptiva e no LDP (DIRAÇOǦLU et al, 2016;KIVRAK et al, 2016;NAHMAN-AVERBUCH et al, 2016).…”
Section: Sensibilidade à Dor (Limiar De Dor à Pressão)unclassified
See 1 more Smart Citation